OVERTHINKING IN THE QUR’AN AND TAWAKKAL AS A QUR’ANIC SOLUTION: A THEMATIC TAFSIR STUDY - Niken Meysha Alviani; Syafii Syafii; Rudi Edwaldo Jasmit; Azhar Ibrahim (STAI Asy-Syukriyyah, 2026)
Overthinking has emerged as a significant psychological problem, marked by excessive rumination, anxiety, and persistent negative thoughts that disrupt mental and spiritual well-being. This study explores the Qur’anic understanding of overthinking through the concepts of al-ẓann (negative assumptions) and al-khauf (excessive fear), while examining tawakal (trust in God) as its spiritual remedy. Using a qualitative library-based approach and the thematic exegesis (tafsīr maudhu‘ī) method, the study analyzes Qur’anic verses alongside classical and contemporary interpretations and relates them to modern psychological theories of anxiety and rumination. The findings indicate that overthinking originates from distorted cognitive and emotional patterns represented by al-ẓann and al-khauf. In this context, tawakalfunctions as a psycho-spiritual mechanism that harmonizes rational effort with reliance on God, helping reduce anxiety, regulate emotions, and promote mental stability in contemporary life.